Effects of mixed cropping with cowpea and nitrogen source on growth and yield of sunflower (Helianthus annuus L.) - Morsal, Nizar E. A.; Mohamed, Ibrahim E.; Eltayeb, Eltohami I.; Gangi, Ali S. (Gezira Journal of Agricultural Science; Vol 14 No 1 (2016), 2016)
Field experiments were conducted during winter (2011/12) and summer (2012/13) seasons. The objective of the study was to examine the effects of mixed cropping with cowpea, nitrogen and chicken manure on growth and yield of sunflower. Randomized complete block design with four replicates was used. The experiment comprised 8 treatments; two sunflower cultivars namely, Hysun33 and Damazin-1, and three nitrogen sources viz : mixed cropping with cowpea, urea (43kgN/ha), chicken manure (5t/ha) plus control. Results showed that the two cultivars were significantly different in plant height, days to 50% flowering, 1000-seed weight and empty seed percentage in both seasons. Hysun33 had taller plants, late to flower, heavier seeds and lower empty seeds percentage than Damazin-1. They were also significantly different in LAI, head diameter, number of filled seeds/ head and total yield in the summer season only. Fertilizers significantly influenced plant height and stem diameter in both seasons. In the winter season, however, fertilizers had significantly affected LAI, days to 50% flowering, head diameter, number of filled seeds/head and total yield. Chicken manure resulted in the tallest plants and largest stem diameter in both seasons. Chicken manure expressed the largest LAI, biggest head diameter, highest number of filled seeds/head and highest total yield. The three-way interaction(seasonx fertilizerx cultivar) showed significant effects on percentage of empty seeds and total yield. The highest total yield was obtained by Hysun33 in the summer season when chicken manure was applied. The mean total yield of the summer season was higher than that of the winter season. To obtain high total yield of sunflower, it is recommended that sowing should be commenced during the summer season and chicken manure should be applied at the rate of 5 t/ha for both Hysun33 and Damazin-1